PRODUCTIVITY OF SOYBEAN CULTIVARS IN THE 2020/21 AGRICULTURAL YEAR WITH AND WITHOUT SUPPLEMENTARY IRRIGATION IN THREE SEEDING SEASONS IN THE CENTRAL REGION OF RIO GRANDE DO SUL - Boff de Oliveira, Zanandra; Eduardo Knies, Alberto (Revista Brasileira de Engenharia de Biossistemas, 2021)
This study aims to evaluate the influence of supplemental irrigation and three sowing times (5/11/20; 3/12/20 and 14/1/21) on the yield of soybean cultivars from different GMRs (5.0; 5.5; 6.3), in the edaphoclimatic conditions of the central region of RS for the 2020/21 agricultural year. The field experiment was installed in an experimental area at Uergs Cachoeira do Sul - RS. Supplemental irrigation provided positive increments in all soybean yield components, providing average yield gains of around 37%, making it possible to reach a yield of up to 6757.5 kg ha-1 in the 5/11 sowing. Cultivars of GMR 5.5 and 6.3 were more productive regardless of the water regime and for the three sowing dates. There was a reduction in all components of soybean yield and productivity on average of 32 kg ha day-1 with the delay in sowing from 5/11 to 14/1.